Examining the Jaranan Singo Suryo Bawono Art in Pasuruan Regency from an Accounting Perspective - Hikma, Divil; Hwihanus, Hwihanus (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The traditional art of Jaranan Singo Suryo Bawono is a form of local cultural heritage in Pasuruan Regency, East Java, which combines elements of dance, music and drama. Apart from functioning as entertainment, this art also has deep social and cultural value, such as preserving traditions, strengthening local identity, and empowering the community's economy. This research aims to examine the financial management of the Jaranan Singo Suryo Bawono arts group, which until now still uses simple manual recording without following formal accounting standards. The research approach used is descriptive qualitative with interview and documentation methods. The research results show that the financial management carried out still has many weaknesses, such as a lack of transparency and accountability, which can hinder the sustainability of the arts. For this reason, it is recommended that this arts group implement the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) and diversify income through collaboration with the government and sponsors.